USULAN PERBAIKAN KUALITAS PRODUK MIE INSTAN DENGAN METODE SIX SIGMA (DMAIC) DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) DI PT. XY - Ika Roma Rohami Nasution; Khawarita Siregar; Anizar Anizaar (Departemen Teknik Industri Universitas Sumatera Utara, 2013)
XY Company is a food industry, which produced instant noodles. The problem which faced by company is highly percentage of defective product of about 8.9% which limit as stipulated by company is 3% of total production. The aim of the research is to reduce the quantity defect product and gives recomendation about repaiment proposed the quality of instant noodles using six sigma method. The result of the research was DPMO value about 17997.4234 with σ value 3.5, which world industry value level of about 6 σ (3.4 DPMO).Capability process was about 0.513 and index capability process was about 0.36 which showed the capability process was still low and average of processing still produced unspecifications product. Based on analyze step, the mostly defect product are broken noodles, defect packing, contamination. Failure Mode and Effect Analysis (FMEA) step obtained the most potential causing factor was loose chain cutter machine with RPN (Risk Priority Number) value 240. ANAVA test showed there was a significant factor between long sealer temperature and end sealer temperature. Recommendation for setting long sealer machine is 2150C, speed for cutter machine is 650 rpm and end sealer temperature is 1640C.